LUMBAR LORDOSIS AND SACRAL SLOPE ANGLE MEASUREMENTS ACCORDING TO ADULT AGE GROUPS: A MORPHOMETRIC STUDY - (:unkn) unknown (My University, 2015)
Amaç: Bu çalışmanın amacı sağlıklı erişkin yaş gruplarına ve cinsiyete göre lomber lordoz (LL) ve sakral slop (SS) açılarını ve birbirleri ile olan ilişkiyi incelemektir.Materyal-Metod: Retrospektif olarak 132 hasta dosyası incelendi. Hastalar yaş gruplarına göre 3 gruba 18-40, 41-60 ve 6180 olarak ayrıldı. İnce kesit lomber vertebral bilgisayarlı tomografi çekilen hastalar çalışmaya alındı. Sonuçlar: 46 hasta (% 34.8) 18-40 yaş arasında, 46 hasta (% 34.8) 41-60 yaş arasında ave 40 hasta (30.3%) 61-80 yaş arasında idi. Cinsiyetler arası yaş farkı istatistiksel olarak anlamlı değildi. Karşılaştırma sonucunda LL ve SS değerleri anlamlı olarak 6180 yaş aralığında yüksek olarak bulundu (p<0.001). Analizlere göre yaş(p<0.001), LL (p<0.001) ve SS (p<0.001) değerleri kadınlarda erkeklere göre daha büyük olarak bulundu. LL ve SS değerleri birbirleri ile doğru orantıda hareket ettikleri anlaşıldı.Çıkarım: LL ve SS değerleri tüm yaş gruplarında birbirleri ile anlamlı ve güçlü pozitif birliktelik göstermekte ve 61-80 yaş grubunda anlamlı olarak daha yüksek değerlere çıkmaktadır

Purpose: The aim of the study is to evaluate lumbar lordosis (LL) and sacral slope (SS) angle values according to healthy adult age groups, gender and correlations with each other.Materials-Methods: We inspected 132 patients' datas retrospectively from the patient files. The patients were divided into 3 age groups as 18-40, 41-60 and 61-80. Patients who had been imaged with lumbar vertebral multi-sliced computed tomography were included.Results: Forty-six participants (34.8 %) were between 18-40 years, 46 cases (34.8 %) between 41-60 years, and 40 cases (30.3 %) between 61-80 years. There was no significant difference between the age groups regarding gender. The comparisons revealed that both LL, and SS values were significantly higher in 61-80 years (p<0.001 for both). According to the analyses, age (p<0.001), LL (p<0.001), and SS (p<0.001) values were significantly higher in females when compared to males. LL and SS values showed statistically significant and strong positive correlation with each other.Conclusion: LL and SS values showed statistically significant and strong positive correlation with each other through all age groups additionally significantly higher in 61-80 years
ERİŞKİN YAŞ GRUPLARINA GÖRE LOMBER LORDOZ VE SAKRAL SLOP AÇILARININ ÖLÇÜMÜ: MORFOMETRİK ÇALIŞMA
Keywords: Cerrahi